CLINICAL AND HISTOPATHOLOGICAL EVALUATION OF USING PLATELET-RICH PLASMA AND PLATELET-RICH FIBRIN MATRIX IN TREATMENT OF INDUCED CHRONIC OPEN WOUNDS IN BUCKS - Khalaf, Falah H; Salih, Serwa Ibrahim (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study was designed to identify the effectiveness of platelet-rich plasma gel (PRP) and platelet-rich fibrin matrix (PRF) application on the induced open chronic full-thickness cutaneous wounds in goats. Methods: A total of 24 adult apparently healthy local breed bucks were used in this study. PRP gel and PRF matrix were prepared from whole blood at the time of treatment, four square full-thickness skin wounds (4 cm Ã— 4 cm) on the dorsal sides of the back of each animal were created, by daily scratched to interrupt healing process continuation to prolong inflammatory reaction to form chronic wound, this surgical procedure was continued for 8 weeks to ensure the traditional chronicity wounds, after that they were treated by PRP gel in the first group (n=12), while PRF matrix was used in the second group (n=12). Each group was also subdivided into treatment (n=2 wounds) and control group (n=2 wounds) in each animal. The healing process was evaluated by clinical examination during experimental period and histologically in day 7, 14, 28, and 45 post operation. Conclusion: Both groups showed faster tissue repair and epithelialization in treatment groups compared to control groups. The results of this study confirmed PRP gel and PRF matrix application improved and accelerated cutaneous open chronic wound healing.